2016
DOI: 10.1080/21645515.2016.1191717
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of trivalent influenza vaccines in patients with chronic kidney disease undergoing hemodialysis: MF59-adjuvanted versus non-adjuvanted vaccines

Abstract: The MF59-adjuvanted influenza vaccine showed better immunogenicity than the non-adjuvanted influenza vaccine in CKD patients undergoing HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…As with hepatitis B vaccines, the use of various adjuvants (like MF59‐FLUA, AS02‐ or AS04c) increase seroconversion rates compared to the nonadjuvanted ones in various groups of ESRD patients from various countries. In a comparative study of an adjuvanted vs a nonadjuvanted trivalent vaccine against influenza, the seroconversion rate of all 3 vaccine strains at 1 month postvaccination was significantly higher in the MF59‐adjuvanted group than in the nonadjuvanted group (47.7% vs 17.4%, A/H1N1; 42.0% vs 16.3%, A/H3N2; 31.8% vs 7.0%, B, P < .01) . Similar results have been shown in other equivalent studies …”
Section: Influenzasupporting
confidence: 86%
“…As with hepatitis B vaccines, the use of various adjuvants (like MF59‐FLUA, AS02‐ or AS04c) increase seroconversion rates compared to the nonadjuvanted ones in various groups of ESRD patients from various countries. In a comparative study of an adjuvanted vs a nonadjuvanted trivalent vaccine against influenza, the seroconversion rate of all 3 vaccine strains at 1 month postvaccination was significantly higher in the MF59‐adjuvanted group than in the nonadjuvanted group (47.7% vs 17.4%, A/H1N1; 42.0% vs 16.3%, A/H3N2; 31.8% vs 7.0%, B, P < .01) . Similar results have been shown in other equivalent studies …”
Section: Influenzasupporting
confidence: 86%
“…The CDC reports similar vaccine effectiveness in successive years (47% versus 40%, respectively); virulence has not, as of yet, been reported for 2016-2017 (21). We had postulated that the effect of the high-dose vaccine would be greater in older individuals in light of a number of studies that have shown a decline in the seroresponse to the influenza vaccine with age (7,13,15,22). Although the magnitude of reduced risk of high-dose versus standard dose vaccine with hospitalization was larger in the $65 versus ,65-year-old age groups in both influenza seasons, an interaction of age with vaccine type was not statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…Adjuvanted vaccines contain a high purified protein (e.g., squalene or tocopherol) that stimulates the immune response, and they have an advantage over the high-dose vaccine of being able to be produced in large quantities relatively quickly, because they do not require as much influenza antigen. Studies in the dialysis population have shown a greater seroresponse to an adjuvanted influenza vaccine compared with the standard dose vaccine (9,22,29,30), although no study has assessed effects on clinical outcomes (22). A comparison of adjuvanted and high-dose vaccines has also not been done in the dialysis population or the general population.…”
Section: Discussionmentioning
confidence: 99%
“…43 For example, immunity resulting from single-dose vaccines may wane before the end of an influenza season, leading to suggestions that patients on dialysis should receive high-dose or adjuvanted influenza vaccines. 44,45 Given that vaccines have not been developed for the majority of viruses responsible for ILI, the nephrology community should expect at most a modest benefit from any dialysis population-wide influenza vaccination program, as well as supporting future efforts to explore the immune response to vaccinations in such patients.…”
Section: Discussionmentioning
confidence: 99%